Recycling of date palm foliar waste into a biofertilizer using siliceous minerals and Trichoderma lignorum - Natalia V. Zaimenko; Nataliia P. Didyk; Nataliia A. Pavliuchenko; Iryna P. Kharytonova; Alla V. Liubinska; Olena P. Yunosheva (International Journal of Recycling of Organic Waste in Agriculture)
Purpose: Palm pruning produces a huge amounts of wastes containing high amount of crude fiber, which slows down its decomposition in soil. This study aims to optimize the process of date palm leaves recycling into an effective biofertiliser using inoculation with Trichoderma lignorum, siliceous minerals and organic fertilizers.